2013
DOI: 10.1262/jrd.2012-134
|View full text |Cite
|
Sign up to set email alerts
|

Effect of 7,8-Dihydroxyflavone as an Antioxidant on <i>In Vitro</i> Maturation of Oocytes and Development of Parthenogenetic Embryos in Pigs

Abstract: One of the factors that impairs in vitro produced porcine embryos is the oxidative stress that is mainly caused by the imbalance between reactive oxygen species (ROS) generation and antioxidants activity, especially that of glutathione (GSH). Here, we examined the effect of 7,8-dihydroxyflavone (7,8-DHF), a kind of flavonoid antioxidant, on porcine oocyte maturation and its developmental competence. Porcine oocytes were cultured in media supplemented with 0, 1, 5 and 10 μM 7,8-DHF during both in vitro maturati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 57 publications
0
22
1
Order By: Relevance
“…Yet, regardless of the use of one or two associated antioxidants, these substances may have other benefits. The flavonoids (quercetin and resveratrol), cysteamine (via GSH), vitamin C and carnitine interact with gene expression, altering the expression of certain genes (Bax, Blc‐2, TP53, Oct‐4, Cx‐43, IGF‐1 and Glut‐1), which may cause a likely reduction in cell damage (Choi et al., ; Elamaran et al., ; Kawashima et al., ; Mukherjee et al., ; You, Lee, Hyun, & Lee, ). The antioxidants quercetin, resveratrol, vitamin C and carnitine can also present a protective effect on mitochondrial functions (Carrasco‐Pozo, Mizgier, Speisky, & Gotteland, ; Lee., Li, Chen, & Chang, ; Somfai et al., ; Sugiyama et al., ) to new mitochondrial synthesis in oocytes from antral follicles cultured in vitro with resveratrol.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Yet, regardless of the use of one or two associated antioxidants, these substances may have other benefits. The flavonoids (quercetin and resveratrol), cysteamine (via GSH), vitamin C and carnitine interact with gene expression, altering the expression of certain genes (Bax, Blc‐2, TP53, Oct‐4, Cx‐43, IGF‐1 and Glut‐1), which may cause a likely reduction in cell damage (Choi et al., ; Elamaran et al., ; Kawashima et al., ; Mukherjee et al., ; You, Lee, Hyun, & Lee, ). The antioxidants quercetin, resveratrol, vitamin C and carnitine can also present a protective effect on mitochondrial functions (Carrasco‐Pozo, Mizgier, Speisky, & Gotteland, ; Lee., Li, Chen, & Chang, ; Somfai et al., ; Sugiyama et al., ) to new mitochondrial synthesis in oocytes from antral follicles cultured in vitro with resveratrol.…”
Section: Discussionmentioning
confidence: 99%
“…For evaluation, the oocytes (10–15 oocytes) were incubated in 10 μM 2′,7′‐dichlorodihydrofluorescein diacetate (H 2 DCFDA, diluted in DMSO) in PBS/PVA, for 20 min in a cell culture incubator (38.5°C; 5% CO 2 in air) to determine ROS levels (Mukherjee et al., ; Wang et al., ). For GSH levels evaluation followed the same procedure, but the oocytes were incubated in 10 μM 4‐chloromethyl‐6,8‐difluoro‐7‐hydroxycoumarin—Cell Tracker Blue—diluted in DMSO (Thermo Fisher Scientific Inc. USA) (Choi et al., ; Kwak et al., ; Mukherjee et al., ; Wang et al., ). As technical control, oocytes stained for ROS or GSH were also evaluated in groups cultured with 0.5 mg/ml catalase (diluted in H 2 O) or 0.003% hydrogen peroxide (H 2 O 2 , diluted in H 2 O), respectively (Nasr‐Esfahani, Aitken, & Johnson, ).…”
Section: Methodsmentioning
confidence: 99%
“…(), while the other four ( YWHAG/RPL4/HRPT1/PPIA ) are different. The reason we selected these seven genes for RT‐qPCR normalization is that they were reported within recent 5 years (year 2012 to 2015) (Choi et al., ; Gu et al., ; Kuchipudi et al., ; Nagyova et al., ; Park et al., ; Santiquet et al., ; Spate et al., ), comparing to the report published in year 2007 (Kuijk et al., ). In addition, YWHAG, one candidate gene included in the present study but not in Kuijk et al.…”
Section: Discussionmentioning
confidence: 99%
“…All seven candidate genes ( GAPDH, 18S, YWHAG, BACT, RPL4, HRPT1 and PPIA ) were chosen primarily based on their relatively stable expression in different types of pig tissues, cells and oocytes, as reported previously (Choi et al., ; Gu et al., ; Kuchipudi et al., ; Nagyova, Nemcova, Mlynarcikova, Scsukova, & Kalous, ; Park et al., ; Santiquet, Robert, & Richard, ; Spate et al., ). Detailed information on these genes was summarized as in Table .…”
Section: Methodsmentioning
confidence: 99%
“…Thus in PCOS patients, in-vitro maturation (IVM), not only rescues oocytes from ovarian damage, but also compensates the deficiency of antioxidants activity, preserves immature oocytes from unfavorable in-vivo maturation, and avoids ovarian hyperstimulation (Nikmard et al, 2017;Savic-Radojevic et al, 2015;Zhao et al, 2009). However, the activation of the oxidative stress pathway in the IVM medium is unavoidable (Choi et al, 2013). Recent studies showed that the environmental factors, such as light and culture medium composition, can induce metabolic alterations in the cytoplasm, resulting in mitochondrial dysfunction, augmentation of lipid peroxidation, DNA fragmentation, apoptosis, and embryo growth arrest in cultured oocytes (Agarwal, Said, Bedaiwy, Banerjee, & Alvarez, 2006).…”
Section: Introductionmentioning
confidence: 99%